2004
DOI: 10.1002/bsl.575
|View full text |Cite
|
Sign up to set email alerts
|

The New Orleans Forensic Aftercare Clinic: a seven year review of hospital discharged and jail diverted clients

Abstract: This paper provides a review of the Forensic Aftercare Clinic Conditional Release Program (FAC), which has been operating since December, 1995, in New Orleans, LA. The FAC is a community based program that provides clinical, rehabilitative, and supervisory services to individuals who have been found not guilty by reason of insanity or unrestorably incompetent to proceed and who have been discharged from inpatient settings or diverted from jail settings and placed on conditional release by district court orders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 8 publications
1
47
1
Order By: Relevance
“…Comparisons between international studies are however difficult due to differences in several core aspects, such as the definition of the population, follow-up periods, outcome measures, settings and legal regulations (Lund, Forsman, Anckarsäter, & Nilsson, 2012). With regard to differences in outcome measures, most international studies investigating recidivism used reconviction as outcome measure, while some studies used re-arrest (Bertman-Pate et al, 2004) or an even broader definition of recidivism such as re-admission in a forensic hospital or any police contact (Lee, 2003). The more stringent definitions will logically result in lower recidivism rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons between international studies are however difficult due to differences in several core aspects, such as the definition of the population, follow-up periods, outcome measures, settings and legal regulations (Lund, Forsman, Anckarsäter, & Nilsson, 2012). With regard to differences in outcome measures, most international studies investigating recidivism used reconviction as outcome measure, while some studies used re-arrest (Bertman-Pate et al, 2004) or an even broader definition of recidivism such as re-admission in a forensic hospital or any police contact (Lee, 2003). The more stringent definitions will logically result in lower recidivism rates.…”
Section: Discussionmentioning
confidence: 99%
“…Literature demonstrates that revocations for rule violations are higher than revocations for acquisition of new criminal charges (Vitacco, Vauter, Erickson, & Ragatz, 2014;Wiederanders, 1992). Revocation rates of rule violations range from 5% to 49% (Bertman-Pate et al, 2004;Callahan & Silver, 1998;Green et al, 2014;Manguno-Mire, Coffman, DeLand, Thompson, & Myers, 2014;Vitacco et al, 2008;Vitacco et al, 2014;Wiederanders, Bromley, & Choate, 1997) over different follow-up periods ranging from 1.7 to 5.1 years.…”
Section: Medium Security Treatment and Recidivism Ratesmentioning
confidence: 97%
“…When the original study by Bertman-Pate and colleagues (2004) was published, criminal defendants in Louisiana who were unrestorably incompetent and not in need of inpatient treatment could be released on probation under state supervision (La C.Cr.P. Art.…”
Section: Conditional Release In Louisianamentioning
confidence: 99%
“…The majority of studies focus on the conditional release of NGRI acquittees (Callahan & Silver, 1998; Monson, Gunnin, Fogel, & Kyle, 2001; Parker 2004; Vitacco et al ., 2008, 2011, 2013), although Bertman-Pate and colleagues (2004) and Wilson and colleagues (1995) evaluated conditional release in a mixed sample of mentally disordered offenders.…”
mentioning
confidence: 99%
“…For instance, Wiederanders, Bromley, and Choate (1997) reported 'annualized' rates of violent recidivism amongst 'not guilty by reason of insanity' (NGRI) patients in the community in three U.S.A. states varying from 3.4 to 7.8%. More recently, Bertman-Pate et al (2004) found a 10% rate over a 22.6 month follow-up. Lee (2003) in an 11 year study found that successful community outcome was related to duration of previous inpatient treatment, with longer admissions associated with less violence.…”
Section: Introductionmentioning
confidence: 95%